The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/microorganisms8091290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lentil Genotype on the Colonization of Beneficial Trichoderma Species and Biocontrol of Aphanomyces Root Rot

Abstract: Trichoderma species are opportunistic plant symbionts that are common in the root and rhizosphere ecosystems. Many Trichoderma species may enhance plant growth, nutrient acquisition, and disease resistance, and for these reasons, they are widely used in agriculture as biofertilizers or biocontrol agents. Host plant genotype and other microorganisms, such as root pathogens, may influence the efficacy of Trichoderma inoculants. Aphanomyces euteiches is an important soil-borne oomycete in western Canada that caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…Different Trichoderma species or strains can have a diverse impact on different crop species, or even genotypes of the same crop, as observed in tomato in which T. afroharzianum T22 and Trichoderma atroviride P1, diversely affected plant growth and resistance against Botrytis cinerea , depending upon the tomato genotype (Tucci et al, 2011 ). Furthermore, the crop genotype was found to significantly influence the colonization by different Trichoderma strains in the rhizosphere of lentils (Bazghaleh et al, 2020 ). Trichoderma may promote plant endogenous defenses against biotic (phytopathogenic fungi) and abiotic stress factors by induced local or systemic resistance (ISR), similar to those activated by plant growth promoting rhizobacteria (PGPR) that result in the priming of the plant to subsequent attacks by pathogens or other parasites (Harman et al, 2004 ; Lorito et al, 2010 ; Hermosa et al, 2013 ; Conrath et al, 2015 ; MartĂ­nez-Medina et al, 2017 ; Adnan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different Trichoderma species or strains can have a diverse impact on different crop species, or even genotypes of the same crop, as observed in tomato in which T. afroharzianum T22 and Trichoderma atroviride P1, diversely affected plant growth and resistance against Botrytis cinerea , depending upon the tomato genotype (Tucci et al, 2011 ). Furthermore, the crop genotype was found to significantly influence the colonization by different Trichoderma strains in the rhizosphere of lentils (Bazghaleh et al, 2020 ). Trichoderma may promote plant endogenous defenses against biotic (phytopathogenic fungi) and abiotic stress factors by induced local or systemic resistance (ISR), similar to those activated by plant growth promoting rhizobacteria (PGPR) that result in the priming of the plant to subsequent attacks by pathogens or other parasites (Harman et al, 2004 ; Lorito et al, 2010 ; Hermosa et al, 2013 ; Conrath et al, 2015 ; MartĂ­nez-Medina et al, 2017 ; Adnan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…By capitalizing on the influence of priority effects, microbial inputs at an early plant stage may have large effects in community assembly and on disease protection [69]. Community assembly can also be governed by multiple processes, including host genotype [77,78] and its interaction with priority effects [66]. Such assembly dynamics can, in turn, influence the community invasibility and dictate the establishment and success of the biocontrol agent [79].…”
Section: Priority Effectsmentioning
confidence: 99%
“…In a recent study, Wei et al (2019) have shown that cotton cultivars differing in their resistance to verticillium wilt have distinct rhizosphere microbiome compositions. Similarly, the root endophyte composition of carrot (Abdelrazek et al, 2020) and lentil (Bazghaleh et al, 2020) cultivars could be related to the plant resistance levels. In addition, it was shown that plant domestication and resistance breeding are actively shaping the plant microbiome (Mendes et al, 2018b;Wagner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%